2021
DOI: 10.1039/d1ra01173a
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into targeting of the colchicine binding site by ELR510444 and parbendazole to achieve rational drug design

Abstract: Crystal structures of tubulin complexed with ELR510444 and parbendazole facilitate the design of novel colchicine binding site inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…25,26 Many studies have shown that colchicine destabilises microtubules in the cytoskeletal structures. 6,10,34,35 Cell morphology images confirmed that colchicine changed the cytoskeletal structures, proving that colchicine could inhibit microtubule polymerisation at the nanoscale. Colchicine has been shown to be a depressant in cancer treatment.…”
Section: Biomechanical Properties Of Cells Have Been Identifiedmentioning
confidence: 84%
See 1 more Smart Citation
“…25,26 Many studies have shown that colchicine destabilises microtubules in the cytoskeletal structures. 6,10,34,35 Cell morphology images confirmed that colchicine changed the cytoskeletal structures, proving that colchicine could inhibit microtubule polymerisation at the nanoscale. Colchicine has been shown to be a depressant in cancer treatment.…”
Section: Biomechanical Properties Of Cells Have Been Identifiedmentioning
confidence: 84%
“…Cell mechanics and disease states are influenced by changes in cytoskeletal architecture induced by chemotherapy regimens and anticancer drugs 25,26 . Many studies have shown that colchicine destabilises microtubules in the cytoskeletal structures 6,10,34,35 . Cell morphology images confirmed that colchicine changed the cytoskeletal structures, proving that colchicine could inhibit microtubule polymerisation at the nanoscale.…”
Section: Discussionmentioning
confidence: 98%
“…Among recently reported colchicine-binding site inhibitors are dihydroquinoxalinone 6a (SB226) [ 41 ], pyrrolopyrimidine 6b [ 42 ] and sulfonamides 7a and 7b [ 43 , 44 ]. Interestingly 5 , 6a , 6b , 7a and 7b , together with the recently reported quinazoline 6c [ 45 ], lack the characteristic 3,4,5-trimethoxyaryl pharmacophore.…”
Section: Introductionmentioning
confidence: 99%
“…The first interaction zone comprises the COL pocket, whereas the second zone is populated by chemical entities that connect the two aforementioned sites. The proximity between these sites has recently led to the rational design of compounds that could occupy the benzimidazole and COL sites in order to enhance their anticancer activity . Moreover, the benzimidazole site exhibits significant variations in the amino acid composition among some target and off-target β-tubulin isotypes. In an earlier study, our research group found that the substitution of Glu with Ala at position 198 in the β-tubulin isotype VI (βVI, TUBB1 gene) diminishes the binding affinity of CBZ derivatives to this off-target tubulin, which is normally expressed in blood leukocytes and bone marrow. , …”
Section: Introductionmentioning
confidence: 99%